Growth rate of the benthic foraminifera Amphistegina lobifera exposed to electric current, May 2023 - Rebecchi, Federica; Lattanzi, Davide; Abramovich, Sigal; Ambrogini, Patrizia; Frontalini, Fabrizio; Schmidt, Christiane (In: Rebecchi, F et al. (2025): Effects of electric current on growth, chlorophyll a content, pulse amplitude modulation response, and new chamber formation of the foraminifera Amphistegina lobifera [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983600, 2025)
This dataset provides measurements of the growth rate of the benthic foraminifera Amphistegina lobifera, exposed to electric currents. The data were collected after a one-month period in May 2023 during the second of a two-part experiment. Growth measurements were taken from all individuals by capturing light microscope images (Zeiss Stereomicroscope Discovery.V8 and Canon EOS 600D camera) before and after the experiment, followed by analysis using ImageJ software. The diameter of each foraminifer was measured, and growth rates were calculated. This dataset presents results on the potential effects of electric currents in enhancing the growth of benthic foraminifera.
Keywords: Benthic foraminifera; chlorophyll-a; electric current; growth rate; Laboratory experiment; PAM fluorometry